2016
DOI: 10.1111/gtc.12446
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fructose‐induced hepatocellular carcinoma development manifested in mice lacking apoptosis inhibitor of macrophage (AIM)

Abstract: The consumption of fructose, including the use of high-fructose corn syrup as a sweetener, has increased continuously in recent decades. Although the involvement of fructose in the development of metabolic diseases has been emphasized recently, whether fructose intake increases susceptibility to steatosis-associated hepatocellular carcinoma (HCC) is unclear. Here, we investigated this issue using mice lacking a circulating protein, apoptosis inhibitor of macrophage (AIM, encoded by cd5l). AIM does not induce c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 59 publications
0
29
0
1
Order By: Relevance
“…In addition, the present results could help to shed light on the recently evidenced cytotoxic effect of fructose and its metabolites in the induction of hepatocyte carcinogenesis [50]. …”
Section: Discussionmentioning
confidence: 90%
“…In addition, the present results could help to shed light on the recently evidenced cytotoxic effect of fructose and its metabolites in the induction of hepatocyte carcinogenesis [50]. …”
Section: Discussionmentioning
confidence: 90%
“…Indeed, most AIM −/− mice bear multiple HCC tumors when fed an HFD or a high-fructose diet for a year; in contrast, wild-type mice do not develop HCC tumors. 18,21 Overall, AIM prevents HCC tumor development through the elimination of cancerous hepatocytes. In addition, Lozano's group reported that AIM attaches to certain bacteria to induce coagulation, which aids effective bacterial eradication by the immune cells.…”
Section: Aim Influences Disease Progression In An Igm-free Mannermentioning
confidence: 99%
“…CD5-like (CD5L) protein is a soluble glycoprotein, also known as apoptosis inhibitor of macrophage (AIM) (10). CD5L serves diverse roles in the relationship between lipid homeostasis and the immune response (11).…”
Section: Introductionmentioning
confidence: 99%